Development of the first standardised panel of two new microsatellite multiplex PCRs for gilthead seabream (Sparus aurata L.). (10th April 2013) - Lee‐Montero, I.; Navarro, A.; Borrell, Y.; García‐Celdrán, M.; Martín, N.; Negrín‐Báez, D.; Blanco, G.; Armero, E.; Berbel, C.; Zamorano, M. J.; Sánchez, J. J.; Estévez, A.; et al.
Summary The high number of multiplex PCRs developed for gilthead seabream (Sparus aurata L.) from many different microsatellite markers does not allow comparison among populations. This highlights the need for developing a reproducible panel of markers, which can be used with safety and reliability by all users. In this study, the first standardised panel of two new microsatellite multiplex PCRs was developed for this species. Primers of 138 specific microsatellites from the genetic linkage map were redesigned and evaluated according to their genetic variability, allele size range and genotyping reliability. A protocol to identify and classify genotyping errors or potential errors was proposed to assess the reliability of each marker. Two new multiplex PCRs from the best assessed markers were designed with 11 markers in each, named SMsa1 and SMsa2 (SuperMultiplex Sparus aurata). Three broodstocks (59, 47 and 98 breeders) from different Spanish companies, and a sample of 80 offspring from each one, were analysed to validate the usefulness of these multiplexes in the parental assignation. It was possible to assign each offspring to a single parent pair (100% success) using the exclusion method with SMsa1 and/or SMsa2. In each genotyped a reference sample (Ref‐sa) was used, and its DNA is available on request similar to the kits of bin set to genotype by genemapper (v.3.7) software (kit‐SMsa1 and kit‐SMsa2). This will be a robust and effective tool for pedigree analysis or characterisation of populations and will be proposed as an international panel for this species.